1988
DOI: 10.1080/00223980.1988.9915521
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Marijuana Use and Anger

Abstract: The Anger Expression Scale and a questionnaire regarding marijuana usage were administered to 497 undergraduate college students enrolled at a rural university in the midwestern United States. Four levels of marijuana use were defined by the questionnaire: nonuser, occasional user, frequent user, and daily user. No significant main effect was found on the Anger-In or Total Anger Expression scales, but differences among the four levels of use were noted on the Anger-Out scale. The trend analysis showed a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Despite the fact that no significant differences regarding marijuana use were found between users and non-users in this study, some parallels between the two studies can be made. Specifically, Stoner (1987) found that anger scores were significantly higher among the high users of marijuana as compared to the low/non-users.…”
Section: Psychological Factorsmentioning
confidence: 96%
See 2 more Smart Citations
“…Despite the fact that no significant differences regarding marijuana use were found between users and non-users in this study, some parallels between the two studies can be made. Specifically, Stoner (1987) found that anger scores were significantly higher among the high users of marijuana as compared to the low/non-users.…”
Section: Psychological Factorsmentioning
confidence: 96%
“…Marijuana users displayed aggression when angry and that aggression was taken out on other people and the environment when the marijuana use increased (Stoner, 1987). LSD users also had problems with aggression (Welpton, 1968), and anabolic steroid users displayed a variety of aggressive behaviors such as hostility and violence (Chaikin & Telander, 1988;Taylor, 1985).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Measures of marijuana use with college samples often produce categories of users ranging from nonusers to heavy/daily users (Stoner, 1988). To measure marijuana use, we used the Marijuana Use Index in which participants report how frequently they currently ingest marijuana (over past year), as well as if they have used marijuana in their lifetime.…”
Section: Alcohol Use Disorders Identification Test (Audit)mentioning
confidence: 99%
“…To measure marijuana use, we used the Marijuana Use Index in which participants report how frequently they currently ingest marijuana (over past year), as well as if they have used marijuana in their lifetime. Participants were then classified into five groups adapted from the categorization pattern of Stoner (1988): nonusers (i.e., never tried marijuana), past users (i.e., tried but have not used in the last year), occasional users (i.e., less than one time per week), frequent users (i.e., one to five times per week), and daily users (i.e., at least one time per day). In our study, 114 of the total sample of 300 students (38%) were categorized as nonusers, 66 (22%) as past users, 72 (24%) as occasional users, 24 (8%) as frequent users, and 24 (8%) as daily users.…”
Section: Alcohol Use Disorders Identification Test (Audit)mentioning
confidence: 99%